MEKANISME FLUOR MENGHAMBAT KERJA ENZIM AIR LIUR - Melanie S. Djamil (Faculty of Dentistry, Universitas Indonesia, 2015)
As the number of DMF-T remain high, the development continues for its prevention and cures. Fluoride supplement is one of the alternative treatments in tooth decay prevention. Fluoride can suppress the glycolysis cycle by preventing the enolase process, thus preventing 2-P glycerate into PEP. Lack of PEP may cuase the transfer of sugar through PEP phosphotransferase system, in increasing the acid through glycolysis process being reduced. Salivary enzyme such as lactoperoxidase, myeloperoxidase and total salivary peroxidase play an important role in saliva, especially antimicrobial activity. THe enzyme in peroixdase system work with tyocianate (SCN) as a catalisator. In oxidation reaction of hydrogen peroxides to hypotiocianate, the enzyme activate the peroxidases system. FLuoride effect to salivary enzyme activities in certain fluoride concentration can inhibit the activities of peroxidases system. Therefore, in a high caries frequency it is better to avoid fluoride administration.